A development and management framework for a new Octopus vulgaris fishery in South Africa - Oosthuizen, Ané (Rhodes University, Faculty of Science, Department of Ichthyology and Fisheries Science, 2004)
A new policy incorporating an operational protocol was developed for the establishment of new fisheries in South Africa. The common octopus, Octopus vulgaris was used as a candidate species for the project. The operational protocol consisted of a three-phased development framework, namely information gathering (Phase 0), an experimental fishery (Phase 1) and the final implementation of a commercial fishery (Phase 2). The present study focussed on phase 0 of this theoretical framework and protocol and was implemented by using a proposed octopus pot fishery in South Africa as a case study. Phase 0 included a desktop study, information gathering in the field, an economic feasibility study and the formulation of a Fishery Management Plan and experimental design for the fishery. Information gaps identified during the desktop study were addressed during field investigations into the population structure and biology of O. vulgaris along the southeast coast. Immature females were found to use the intertidal area to feed and grow before migrating to the subtidal area to mature and spawn. Mean size differed substantially between intertidal and subtidal areas, with larger octopus found subtidally. Age and growth trials using tetracycline as a marker showed that O. vulgaris deposit daily growth lines in their beaks. A genetic study showed that there is most likely only one panmitic population along the coast. The economic feasibility study indicated that a longline pot fishery could be feasible provided a 30% catch in 6600 pots/month is attained. Only existing, debt-free vessels should be used in this fishery. The Fishery Management Plan proposed in this study includes management measures such as effort limitation of licences and gear, size restrictions, vessel monitoring systems, and observer programmes. Based on the population dynamics and biology of O. vulgaris it is suggested that a precautionary approach to developing fisheries for this species in both the inter- and subtidal areas along the South African coast.
Keywords: Common octopus -- South Africa; Octopus fisheries -- South Africa; Octopus fisheries -- South Africa -- Economic aspects; Fishery management -- South Africa